Research on Design Strategy of Mask Recycling Service Based on Behavior Environment - Wu, Yueqin; Zhang, Hao; Zhang, Miao (Sustainability, 2023)
The global novel coronavirus pandemic has caused a surge in the use of masks worldwide. A large number of used masks that have not been properly handled enter the environment, which caused and will cause serious ecological problems. The purpose of this study is to propose a solution to the problem of mask management from the perspective of science of design, and to build a good mask recycling service design strategy through the combination of design and psychology. Firstly, based on the theory of behavioral environment and field investigation, this study analyzes the correlation between the existing mask recycling device and its recycling efficiency, user behavior psychology and environment, and studies the behavioral scene of mask recycling, and then establishes the center of design strategy implementation. Secondly, a visual guidance system is designed, as is a special recycling device for masks by color psychology and product design. Thirdly, combined with the concept of social innovation service design, the design of a mask recycling strategy is conceived, and the optimization and formulation of mask recycling strategy is demonstrated through stakeholders, user journey maps and service flow charts. Finally, the design strategy is hierarchically established, and the feasibility analysis system model of a mask recycling strategy design is constructed. The data collection is carried out through expert interviews and questionnaires, and the weight is calculated by a fuzzy analytic hierarchy process. The final output comprehensive evaluation results show that the mask recycling strategy constructed in this study has public recognition.